CANDIDURIA- PREVALENCE, SPECIATION AND INTERPRETATION OF SUSCEPTIBILITY PATTERN: A STUDY FROM PUDUCHERRY - S. SRIRANGARAJ; ARUNAVA KALI; M. V. PRAVIN CHARLES (International Journal of Pharma and Bio Sciences, 2015)
Candiduria is a common finding in hospitalized patients, Non-albicans Candida species (NAC) have emerged as a pathogenic fungus group, where speciation is important, due to intrinsic resistance to commonly used azoles. In this study, 5180 urine samples were processed to determine prevalence of candiduria, to characterize and determine their antifungal susceptibility pattern by disk diffusion and E-test method. Out of 5180 urine samples, 2092 grew pathogens. Candida accounted for 2.58% (n=54) of these uropathogens. C.albicans was the commonest urinary pathogen (46.3%, n=25). NAC accounted for 53.7% (n=29) of Candida isolates. C.albicans showed 88% susceptibility to fluconazole and 96% susceptibility to voriconazole. C.tropicalis showed 82.4% sensitivity to fluconazole and 88.2% susceptibility to voriconazole. The results indicate that NAC is emerging and replacing C. albicans as a cause for candiduria. Most of the Candida isolates remained susceptible to commonly used antifungal agents like fluconazole and voriconazole.